1989
DOI: 10.1557/proc-167-137
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion, Reaction and Stability of Metal/Polyimide Interfaces

Abstract: Interfacial reactions of polyimide with several metals have been investigated by XPS and TEM to determine their effects on adhesion and long term stability. It has been found that the polyimide-on-metal interface and the metal-on-polyimide interface are intrinsically different; in the case of PI-on-metal interface, the precursor of polyimide, polyamic acid, reacts with the metal resulting in a strong chemical bond and therefore, higher adhesion strength than the corresponding metal-on-PI interface. Both interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…19 In a high-resolution electron energy loss spectroscopy (HREELS) and ultraviolet photoemission spectroscopy (UPS) study they found Chromium. The chemical interaction between thermally evaporated chromium (which is used as an adhesion promoter and diffusion barrier for copper/polyimide layers 20 ) and polyimide has been a subject of numerous studies. Chromium/polyimide interfaces have been studied mainly by XPS 5, [21][22][23][24][25][26][27] .…”
Section: Introductionmentioning
confidence: 99%
“…19 In a high-resolution electron energy loss spectroscopy (HREELS) and ultraviolet photoemission spectroscopy (UPS) study they found Chromium. The chemical interaction between thermally evaporated chromium (which is used as an adhesion promoter and diffusion barrier for copper/polyimide layers 20 ) and polyimide has been a subject of numerous studies. Chromium/polyimide interfaces have been studied mainly by XPS 5, [21][22][23][24][25][26][27] .…”
Section: Introductionmentioning
confidence: 99%
“…2c, due to the dissolution of the Cu 2 O layer in the organic acid in PI during the imidization process. 17 A point to be noted here is that the surface morphology of the Cu oxide does not seem to affect the peel strength of the Cu/PI interface significantly. As measured by atomic force microscopy (AFM), the surface roughnesses (Ra) for specimens of types A and B were 13.7 nm and 3.1 nm, but their peel strengths were 664.4 J/m 2 and 1062 J/m 2 , respectively, showing no correlation between Ra and peel strength.…”
Section: Effects Of Heat Treatment At 300°c Under 5% O 2 Atmospherementioning
confidence: 64%
“…Adhesion-promoting effect was found to be in the following order CH 2 -CH 2 oNH 2 ⪡OH o-COOH [42]. Another study showed that the polyamic acid creates a stronger bond to metal than cured PI [43], because of reactions occurring between the acid and the metal. Therefore the presence of COOH groups found by ATR can be responsible for the better adhesion of PI1 and thicker transfer at the surface of the counterface in H 2 .…”
Section: Pure Pimentioning
confidence: 98%